Information verification during COVID-19. Comparative analysis in Southern European Countries - Magallón-Rosa, Raúl (2021)
Disinformation poses a challenge for democracies, especially in exceptional periods such as electoral processes but, above all, as a consequence of a global health crisis with no clear end date. The objective of this research is to analyse the type of hoaxes identified during the COVID-19 pandemic in southern European countries (Portugal, Spain, Italy and Greece). To this effect, 936 pieces of disinformation reported by the main verification organizations in those countries were examined between February and August 2020: Observador and Polígrafo (Portugal), Newtral, Maldita and EFE verifica (Spain) Facta, Open, Effecinque and Pagella Politica (Italy) and Ellinika Hoaxes (Greece). As a final conclusion, the presence or absence of a common pattern in the four countries is examined based on the topic of the hoaxes, their distribution channels and how viral they spread abroad. Two axes of disinformation were established: one health-preventive and the other in terms of political polarization.